Validating screening tools for depression in stroke and transient ischemic attack patients. (April 2016) - Prisnie, Joey C; Fiest, Kirsten M; Coutts, Shelagh B; Patten, Scott B; Atta, Callie AM; Blaikie, Laura; Bulloch, Andrew GM; Demchuk, Andrew; Hill, Michael D; Smith, Eric E; Jetté, Nathalie
Objective: The best screening questionnaires for detecting post-stroke depression have not been identified. We aimed to validate four commonly used depression screening tools in stroke and transient ischemic attack patients. Methods: Consecutive stroke and transient ischemic attack patients visiting an outpatient stroke clinic in Calgary, Alberta (Canada) completed a demographic questionnaire and four depression screening tools: Patient Health Questionnaire (PHQ)-9, PHQ-2, Hospital Anxiety and Depression Scale (HADS-D), and Geriatric Depression Scale (GDS-15). Participants then completed the Structured Clinical Interview for DSM-IV (SCID), the gold-standard for diagnosing major depression. The questionnaires were validated against the SCID and sensitivity and specificity were calculated at various cut-points. Optimal cut-points for each questionnaire were determined using receiver-operating curve analyses. Results: Among 122 participants, 59.5% were diagnosed with stroke and 40.5% with transient ischemic attack. The point prevalence of SCID-diagnosed current major depression was 9.8%. At the optimal cut-points, the sensitivity and specificity for each screening tool were as follows: PHQ-9 (sensitivity: 81.8%, specificity: 97.1%), PHQ-2 (sensitivity: 75.0%, specificity: 96.3%), HADS-D (sensitivity: 63.6%, specificity: 98.1%), and GDS-15 (sensitivity: 45.5%, specificity: 84.8%). Areas under the receiver operating characteristic curves were as follows: PHQ-9 86.6%, PHQ-2 86.7%, HADS-D 85.9%, and GDS-15 66.3%. Conclusions: The PHQ-2 and PHQ-9 are both suitable depression screening tools, taking less than 5 minutes to complete. The HADS-D does not appear to have any advantage over the PHQ-based scales, even though it was designed specifically for medically ill populations. The GDS-15 cannot be recommended for general use in a stroke clinic based on this study as it had worse discrimination due to low sensitivity.